ADMINISTRASI DAN SUPERVISI MITIGASI INTOLERANSI KURIKULUM BERBASIS CINTA PADA MADRASAH IBIDAIYAH - Indah Nurhidayah; Andin Salsabila; Ahmad Zainuri; Frika Fatimah Zahra (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to examine the role of administration and supervision in mitigating intolerance issues through the implementation of the Love-Based Curriculum (KBC) in Madrasah Ibtidaiyah. Intolerance is a serious challenge at the primary education level, exacerbated by teaching materials that tend to be monotonous and lacking in context (Sari & Utami, 2021). This study proposes the Love-Based Curriculum (KBC) as an approach that instils empathy and tolerance, in line with the principles of character education based on local culture (Lubis, 2018). The method used was Participatory Action Research (PAR), which actively involved administrators (madrasah principals) and teachers through the stages of problem identification, plan development, training, and reflection (Kemmis & McTaggart, 2014, Arikunto, 2019). The results show that supportive administration (such as the provision of visual media) and mentoring-oriented supervision (Widodo, 2020) succeeded in improving teachers' competence in integrating the value of tolerance. Teachers were able to develop creative media, such as comics, which were effective in fostering students' interest and understanding of inclusive values (Sudjana & Rivai, 201166; Saputra, 2019). Thus, administration and supervision are key to the success of KBC as a strategic effort to preserve national values from an early age.